Functional and aesthetic outcomes of first dorsal metacarpal artery flap for thumb reconstruction: a prospective study - Ravada, Sujana; Mahipathy, Surya Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand Prasath (International Surgery Journal, 2020)
Background: Reconstruction of soft tissue defects of the thumb, with exposure of tendon, joint or bone, has been a challenging problem. Surgical options include local, regional or free flaps. Here, we have evaluated the functional and aesthetic outcomes of first dorsal metacarpal artery (FDMA) island flap in reconstruction of various soft tissue defects of the thumb. Methods: Between January 2018 and January 2019, twenty patients with post-traumatic and post-infective thumb defects underwent FDMA flaps. Sensory function was evaluated with static 2 point discrimination and mobility of the thumb was tested by the Kapandji score. The aesthetic outcome was also assessed. Results: The mean defect size was 39.9×19.95 mm. Eighteen flaps survived completely and one had distal flap necrosis and one had superficial epidermal peeling which was treated conservatively. The mean static two-point discrimination was 9.3 mm. Cortical reorientation was complete in 45%. The average Kapandji score was 7.9. The aesthetic outcome was excellent in ten, good in eight and poor in two subjects. After a mean follow up period of 11.85 months, most patients regained all functions of the thumb and index finger and were pleased with the cosmetic appearance of the flap and donor site. Conclusions: FDMA flap offers a good quality skin cover for small to moderate sized thumb defects. It is a reliable and versatile flap which is sensate and pliable. It gives excellent functional and aesthetic outcomes with minimal or no donor site morbidity.